2022
DOI: 10.1245/s10434-022-12356-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Trial Assessing the Impact of Positive Peritoneal Cytology Conversion on Oncological Outcome in Patients with Endometrial Cancer Undergoing Minimally Invasive Surgery with the use of an Intrauterine Manipulator

Abstract: Background Minimally invasive surgery is the standard approach in early-stage endometrial cancer according to evidence showing no compromise in oncological outcomes, but lower morbidity compared with open surgery. However, there are limited data available on the oncological safety of the use of intrauterine manipulators in endometrial cancer. Patients and Methods This prospective multicenter study included patients with endometrial cancer undergoing laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…However, this association was only observed in early-stage cancer 15 . In line with the latter results, Siegenthaler et al showed that positive peritoneal cytology (PPC) conversion occurred in 8% of endometrial cancer patients following laparoscopic surgery with IU manipulators, which had a negative impact on oncological outcome 16 .…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, this association was only observed in early-stage cancer 15 . In line with the latter results, Siegenthaler et al showed that positive peritoneal cytology (PPC) conversion occurred in 8% of endometrial cancer patients following laparoscopic surgery with IU manipulators, which had a negative impact on oncological outcome 16 .…”
Section: Introductionmentioning
confidence: 76%
“…On the contrary, several research groups have indicated that the use of IU manipulators negatively affects oncological outcome 15,16 . Padilla-Iserte et al showed that the recurrence rate (HR 2.31, 95% CI 1.27-4.20) and survival were worse after TLH with IU manipulator than without manipulator, but no difference in recurrence pattern was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This multicenter prospective trial included 124 endometrial cancer patients undergoing laparoscopic staging surgery with the use of an intrauterine manipulator. 5 Three different sets of peritoneal washings were obtained: at the beginning of the surgical procedure, after insertion of the intrauterine manipulator, and after closure of the vaginal vault. Peritoneal cytology was negative for 98 patients and positive at the beginning of the surgery for 16 patients.…”
Section: Presentmentioning
confidence: 99%